2022
DOI: 10.1001/jama.2022.3271
|View full text |Cite
|
Sign up to set email alerts
|

Association of SARS-CoV-2 Vaccination During Pregnancy With Pregnancy Outcomes

Abstract: IMPORTANCE Data about the safety of vaccines against SARS-CoV-2 during pregnancy are limited.OBJECTIVE To examine the risk of adverse pregnancy outcomes after vaccination against SARS-CoV-2 during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
157
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(173 citation statements)
references
References 25 publications
10
157
4
2
Order By: Relevance
“…In terms of the association of COVID-19 vaccination in pregnancy with adverse pregnancy outcomes, the authors included 157 521 singleton pregnancies, consisting of 28 506 (18.1%) who received at least one dose of COVID-19 vaccine during pregnancy (3.9%, 45.9%, and 50.2% received the first dose in the first, second and third trimester, respectively; 98.3% received an mRNA vaccine) and the remaining women who were not vaccinated during pregnancy, and the results showed that there were no significantly increased risks of preterm birth (adjusted hazard ratio [aHR], 0.98; 95% CI, 0.91–1.05]), stillbirth (aHR, 0.86; 95% CI, 0.63–1.17), small for gestational age (adjusted odds ratio [aOR], 0.97; 95% CI, 0.90–1.04), low Apgar score (aOR, 0.97; 95% CI, 0.87–1.08), or neonatal care admission (aOR, 0.97; 95% CI, 0.86–1.10). 12 Based on the absence of association between COVID-19 vaccination and pregnancy outcomes, their study is also in agreement with Dr. Fell’s recommendation that mRNA vaccines during the second and third trimesters of pregnancy should be considered. 11…”
supporting
confidence: 75%
See 1 more Smart Citation
“…In terms of the association of COVID-19 vaccination in pregnancy with adverse pregnancy outcomes, the authors included 157 521 singleton pregnancies, consisting of 28 506 (18.1%) who received at least one dose of COVID-19 vaccine during pregnancy (3.9%, 45.9%, and 50.2% received the first dose in the first, second and third trimester, respectively; 98.3% received an mRNA vaccine) and the remaining women who were not vaccinated during pregnancy, and the results showed that there were no significantly increased risks of preterm birth (adjusted hazard ratio [aHR], 0.98; 95% CI, 0.91–1.05]), stillbirth (aHR, 0.86; 95% CI, 0.63–1.17), small for gestational age (adjusted odds ratio [aOR], 0.97; 95% CI, 0.90–1.04), low Apgar score (aOR, 0.97; 95% CI, 0.87–1.08), or neonatal care admission (aOR, 0.97; 95% CI, 0.86–1.10). 12 Based on the absence of association between COVID-19 vaccination and pregnancy outcomes, their study is also in agreement with Dr. Fell’s recommendation that mRNA vaccines during the second and third trimesters of pregnancy should be considered. 11…”
supporting
confidence: 75%
“…Additionally, data from the US Vaccine Safety Datalink can inform strategies to increase booster dose vaccinations and effective messaging COVID-19 vaccinations significantly lower the risk of serious illness from COVID-19 in pregnant individuals, and data indicate potential benefits to the developing fetus. 11–13…”
mentioning
confidence: 99%
“…Most of the subjects received the Pfizer/BioNTech or Moderna vaccines, and available data do not demonstrate adverse outcomes or side effects of vaccination during pregnancy [ 20 , 22 , 37 , 38 , 39 , 40 , 41 ]. Shimakaburo et al evaluated the outcomes of 827 completed pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Girardi et al found that COVID-19 vaccination in pregnant and lactating individuals is immunogenic, safe with respect to vaccine-related adverse events and obstetrical and neonatal outcomes, and effective in preventing COVID-19 disease [ 17 ]. In a recent population-based study from Sweden and Norway, among pregnant women, vaccination against SARS-CoV-2 compared with no vaccination was not significantly associated with an increased risk of adverse pregnancy outcomes [ 18 ]. The majority of COVID-19 vaccines used in this study were mRNA vaccines; however, 2% of vaccinees received the Oxford-AstraZeneca adenovirus vector vaccine, and most were vaccinated during the second and third trimesters.…”
Section: Safety and Efficacy Of Covid-19 Vaccine In Pregnant Womenmentioning
confidence: 99%